A Top‐Down Strategy toward 3D Carbon Nanosheet Frameworks Decorated with Hollow Nanostructures for Superior Lithium Storage. (20th September 2016) - Dong, Yanfeng; Yu, Mingliang; Wang, Zhiyu; Liu, Yang; Wang, Xuzhen; Zhao, Zongbin; Qiu, Jieshan
Abstract : Graphene has shown great potential in vast fields due to the unique structure and properties, but its practical application is still hindered by high cost and scarcity in supply. The development of low‐cost substitute of graphene is thus highly desired to meet the practical demand of upcoming applications where extremely physical properties are not absolutely critical. In this work, a top‐down strategy for general synthesis of 3D carbon nanosheet frameworks decorated with metal nanoparticles by a metal nitrate‐assisted polymer‐blowing process is reported. Such architecture provides a promising structural platform for the fabrication of carbon nanosheet frameworks functionalized with metal oxide or carbon hollow nanostructures through subsequent chemical conversion. The unique structures impart intimate structural interconnectivities, highly opened freeway for ionic diffusion, large accessible surface area, as well as high structural stability, opening up a wide horizon for electrochemical applications, for example, high‐energy, long‐life lithium‐ion batteries and lithium–sulfur batteries highlighted in this work. Abstract : 3D carbon nanosheet frameworks decorated with hollow nanostructures of metal oxides or carbon hollow shells are synthesized using a metal nitrate‐assisted polymer‐blowing process and subsequent chemical conversion. Because of the unique structures, they exhibit superior electrochemical performance as the electrode materials in lithium‐ion and lithium–sulfur batteries.